Zika virus epidemic: an update. Issue 12 (1st December 2016) - Valentine, Gregory; Marquez, Lucila; Pammi, Mohan
ABSTRACT: Introduction: Zika Virus (ZIKV), previously the cause of only rare and sporadic human infections, is now considered a Public Health Emergency of International Concern. Over the past two years, ZIKV has become a pandemic encompassing much of the Americas. ZIKV is now proven to cause microcephaly and ophthalmic anomalies in the newborn. Hydrops fetalis, developmental delay, and other anomalies are increasingly being attributed to ZIKV infection in fetuses and neonates. Sequelae of congenital infection and rapid spread of ZIKV throughout the Americas has catapulted Zika virus concerns to the forefront of the medical community. Areas covered: This review seeks to consolidate ZIKV epidemiology, diagnostic testing methods, CDC screening recommendations, and preventive strategies including potential vaccines. Expert commentary: Many unknowns still exist regarding ZIKV infections and its long-term effects in neonates. In addition, further studies need to evaluate if genomic differences that have occurred from the African to the Asian lineage of the virus have led to increased virulence of the virus. The authors believe that all pregnant women with fetuses showing microcephaly and/or intracranial calcifications should be tested for ZIKV infection if they cannot recall their sexual partner travel history. This change from the current CDCs recommendations could increase substantially the number of pregnant women and neonates, screened for ZIKV.